China's brick history and conservation: laboratory results of Shanghai samples from 19th to 20th century. (1st October 2017) - Shu, C.X.; Cantisani, E.; Fratini, F.; Rasmussen, K.L.; Rovero, L.; Stipo, G.; Vettori, S.
Highlights: The first inquiry into the provenance of bricks in the Western heritage of China. Identified coal-residue bricks and the potential Russian sources. Proposed new perspectives on the modern revolution of China's brick history. Revealed the present condition of modern Shanghai's bricks for conservation. Abstract: Fired bricks have been used for construction purposes in China for at least two thousand years. Since the mid-19th century the manufacture of bricks has shifted from an old to a new system. The unique Chinese blue brick has been gradually replaced by the European red brick and other modern products. This study focuses on Shanghai as a representative city in that transitional period, aims at addressing the true condition of the modern changes in China's brick history and the heritage today. The paper presents the first results of an interdisciplinary investigation. Fourteen brick samples and one sample of raw material were studied with regard to the mineralogical, petrographic, chemical, physical, mechanical characteristics, and the maximum firing temperature. It also makes measurements of the presented soluble salts in the altered brick samples. Preliminary conclusions are drawn with regard to three critical issues: the provenance of the bricks, the hitherto undocumented changes in the manufacturing technology, and the condition of the brick material in terms of conservation.